Examining Ownership Structure's Impact on Sustainability Disclosure to Enhance Corporate Value: Evidence from Indonesia - Lestari, Rahayu; Suwadji, Sukma Annisa; Muthmainnah, Dewi Refianingrum; Sriwulandari, Eno; Kusuma, Indra Wijaya; Frendy, Frendy (The Indonesian Journal of Accounting Research, 2025)
This study investigates the impact of ownership structure (foreign, government, and public ownership) on sustainability reporting, as measured by Environment, Social, and Governance (ESG) scores. The research sample includes public non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2022 that have ESG scores published by the Thomson Reuters database. The regression analysis results showed that foreign ownership, government ownership, and public ownership have a positive and significant influence on sustainability disclosure. However, sustainability disclosure has been shown to have an adverse effect on firm value. The robustness test analysis of G2SLS supports this finding. The findings of this study suggest that the hypothetically positive impact of sustainability reporting on firm value in a developing economy setting may not be directly reflected in the short term. These results underscore the importance for companies in developing economies to integrate sustainability initiatives more effectively into their long-term strategic objectives, thereby maximizing the potential benefits for firm value. Furthermore, the study provides valuable insights for policymakers and investors by emphasizing the role of ownership structure in driving corporate transparency and sustainability practices.